Determining the Dominant Variable in Budgeting on Performance Effectiveness / PT (Persero) Indra Karya All Branches in Indonesia - Halim, Abdul; Pribadi, Muhammad Iqbal (International Journal Labs, 2023)
This study aims to determine and analyze among the variables: 1) participation in budget preparation, 2) clarity of budget targets, 3) budget feedback, 4) budget evaluation, and 5) level of budget difficulty, which variables have a dominant influence in budgeting on the effectiveness of the performance of PT (Persero) Indra Karya all branches in Indonesia. Using saturated sampling techniques, 41 branch managers of PT (Persero) Indra Karya were obtained throughout Indonesia. Primary data related to research variables were obtained by sending questionnaires directly to respondents via google form. It was further analyzed using multiple linear regression. However, it was previously tested: validity, reliability, linearity, model feasibility, and classical assumption tests include: multicollinearity, heteroscedasticity, normality. The hypothesis was tested using a t-test, The results of this study proved that among the variables: 1) participation in budget preparation, 2) clarity of budget goals, 3) budget feedback, 4) budget evaluation, and 5) budget difficulty; So the variable of participation in budgeting has a significant positive dominant effect in budgeting on the effectiveness of company performance. This is indicated by the value of the regression coefficient is the largest among other variables.